The first record of Callodictya kazeruna Dlabola (Hemiptera, Auchenorrhyncha, Fulgoroidea: Dictyopharidae) from Turkey - Emeljanov, A.F.; Özgen, I.; Gnezdilov, V.M. (Maik Nauka Publishing / Springer SBM, 2017)
Callodictya kazeruna (Dlabola, 1986) described from southern Iran is recorded here for the first time from Eastern Anatolia in Turkey. A key to the two known species of the genus Callodictya Melichar, 1912 is given. © 2017, Pleiades Publishing, Inc.